The Truth and Dare Technique to Embed Writing and Interpersonal Skills - Saichul Kirom; Moh. Hafidz (Penerbit STKIP PGRI Bangkalan, 2026)
Writing and interpersonal skills are two essential abilities that complement each other in effective communication. However, many students in English courses still face difficulties in expressing ideas in writing and interacting confidently. This study aims to describe the implementation of the Truth and Dare technique in integrating students’ writing and interpersonal skills at an English course in Bangkalan. The research employed a qualitative method with a case study design. Data were collected through observation, interviews, and documentation. Research instruments included observation checklists, interview guides, and written documentation. The findings revealed that the Truth and Dare technique enhanced students’ learning motivation, encouraged logical thinking, strengthened collaboration, and created an enjoyable learning atmosphere. Students demonstrated improved ability to construct coherent sentences, express personal ideas honestly, and build positive interactions with peers. This technique proved effective in combining writing instruction with the development of interpersonal skills in a creative and interactive learning environment.